Effect of textile effluent on the yield of jute leaves (Corchorus capsularis) in winter season (Journal of Biodiversity Conservation and Bioresource Management, 2018)
A pot experiment was conducted to observe the effect of textile effluent on the yield of newly developed deshi pat shak-1 (Corchorus capsularis), in winter season by the Bangladesh Jute Research Institute (BJRI). There were six treatments of different effluent level including different proportions of fresh water and Recommended Dose of Fertilizer (RDF). It was observed that all the treatments showed significant positive effect on the yield parameters of jute vegetables over the control on agricultural soils. However, in contaminated soils effluent irrigation showed negative effect over the control. The highest yield of vegetative weight in all soils was observed in the treatment T2 where fresh water + 100% RDF were applied. They were 8.83 t/ha, 8.93 t/ha, 9.07 t/ha and 8.13 t/ha in both agricultural and contaminated soils of Narayanganj and Gazipur respectively with high input cost. But the treated pots with 50% effluent + 50% fresh water + 50% RDF gave second highest vegetative weight with low cost in both the agricultural soils, which were 8.25 t/ha and 7.87 t/ha in Narayanganj and Gazipur agricultural soil, respectively.J. Biodivers. Conserv. Bioresour. Manag. 2018, 4(2): 53-60